Infantile hemangioma: Treatment guidelines - D Sharad Gedam; Umesh Patel (International Journal of Medical Research and Review, 2015)
Infantile hemangioma is most common benign tumour of infancy. Propranolol has become treatment of choice once approved by FDA recently. We are presenting a brief discussion regarding available options for treatment.